Kesiapsiagaan Mitigasi Bencana Banjir Pada Peserta Didik di Sekolah Menengah Pertama - Febrianti Hoar; Sunimbar Sunimbar; Agustinus Hale Manek (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Flood is one of the natural disasters that often occurs in various parts of Indonesia, including in Malaka Regency. The objectives of this study are: 1) to determine the level of knowledge of students regarding flood disaster mitigation at SMP Negeri Satu Atap Wemean; and 2) to determine the preparedness of students at SMP Negeri Satu Atap Wemean in facing flood disasters. This type of research is quantitative descriptive research with samples calculated using the Slovin formula, and the number of samples obtained is 112 students spread across all classes. Data collection techniques are questionnaires, test questions, observation, and documentation. Data analysis techniques include interval scale, descriptive statistics, validity, and reliability tests. The results of the study show that: 1) the level of knowledge of students about flood disasters is included in the moderate category with a percentage of 50% on an interval scale of 0.9 - 1.6 with several respondents of 56 students, which means that students only know flood concept and how often the school is flooded; and 2) student preparedness in facing flood disasters is included in the low or not ready category with an average percentage of 86.7 percent on an interval scale of 0 – 3 with a total of 97 student respondents.